Myosin-II proteins are involved in the growth, morphogenesis, and virulence of the human pathogenic fungus Mucor circinelloides - Trieu, Trung Anh; Nguyen, Phuong Anh; Le, Mai Ngoc; Chu, Huy Nhat (Frontiers in Cellular and Infection Microbiology, 2022)
Mucormycosis is an emerging lethal invasive fungal infection. The infection caused by fungi belonging to the order Mucorales has been reported recently as one of the most common fungal infections among COVID-19 patients. The lack of understanding of pathogens, particularly at the molecular level, is one of the reasons for the difficulties in the management of the infection. Myosin is a diverse superfamily of actin-based motor proteins that have various cellular roles. Four families of myosin motors have been found in filamentous fungi, including myosin I, II, V, and fungus-specific chitin synthase with myosin motor domains. Our previous study on Mucor circinelloides, a common pathogen of mucormycosis, showed that the Myo5 protein (ID 51513) belonging to the myosin type V family had a critical impact on the growth and virulence of this fungus. In this study, to investigate the roles of myosin II proteins in M. circinelloides, silencing phenotypes and null mutants corresponding to myosin II encoding genes, designated mcmyo2A (ID 149958) and mcmyo2B (ID 136314), respectively, were generated. Those mutant strains featured a significantly reduced growth rate and impaired sporulation in comparison with the wild-type strain. Notably, the disruption of mcmyo2A led to an almost complete lack of sporulation. Both mutant strains displayed abnormally short, septate, and inflated hyphae with the presence of yeast-like cells and an unusual accumulation of pigment-filled vesicles. In vivo virulence assays of myosin-II mutant strains performed in the invertebrate model Galleria mellonella indicated that the mcmyo2A-knockout strain was avirulent, while the pathogenesis of the mcmyo2B null mutant was unaltered despite the low growth rate and impaired sporulation. The findings provide suggestions for critical contributions of the myosin II proteins to the polarity growth, septation, morphology, pigment transportation, and pathogenesis of M. circinelloides. The findings also implicate the myosin family as a potential target for future therapy to treat mucormycosis.